Aero Graphene in Modern Aircraft & UAV - Abdullah, Masuk; Husi, Géza (Recent Innovations in Mechatronics, 2022)
The paper focuses on aero graphene and carbon nanotube (CNT) aerogel which will use in aircraft such as battery, engine, pitot probe, wings, fuselage, plane front glass which will also protect the aircraft from rain and wind because of the buoyant force. There are several ways to make aero graphene, but the most common approach includes reducing a precursor graphene oxide solution to make a graphene hydrogel. Through freeze-drying, any solvent is removed from the pores and replaced with air. A new method for producing aero graphene has emerged: 3-D printing. This is a significant scientific achievement. It creates a resin by diffusing graphene in a gel. The graphene resin can be cured into a solid and then dried in a furnace using UV LED light. Aero-graphene coating into the fuselage, wings and front glasses of the cockpit will give a great impact on the next-generation aircraft. Making an aircraft with aero-graphene will give the aircraft a strong and light skeleton.